EFL Teachers' Beliefs and Practices of Written Corrective Feedback in Responding to Students’ Senior Essay Report Writing - Gebreslassie Gebremichael (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2025)
This study mainly focuses on exploring EFL teachers’ beliefs and practices of written corrective feedback in responding to students' senior essay report writing at Aksum University, Ethiopia. Using a qualitative exploratory case study design, this study examines the teachers’ pedagogical beliefs, the strategies they use, the alignment between the teachers’ beliefs and practices and the challenges they experience in responding to students' written activities. Besides, the study is guided by a socio-cultural theoretical framework. Subsequently, findings reveal that EFL teachers recognize the value of written corrective feedback and believe that detailed and comprehensive feedback should be given constructively. However, practically, because of time limitations, large class size, and less engagement of students, they often focus on selective and indirect feedback strategies. In addition, the key challenges identified in this study include teachers’ uncertainty about the effective feedback provision strategies, lack of students’ engagement in the feedback process and inadequate feedback-based training. As a result, the study indicates that the external contextual constraints and those teacher–student related issues should be addressed so as to improve the practices of feedback provisions. Furthermore, findings of the study refine the existing theoretical debates about teachers' beliefs and their actual practices in the feedback process and the controversies in the written feedback literature. Finally, it is recommended that teachers should be given professional training, ensure students' active participation in the feedback process and policy-level intervention is needed to standardize written corrective feedback practices.